Techniques Mostly Used by English Teachers of SMAN 4 Wira Bangsa Melaboh in Teaching Speaking - Ayatullah Rohullah Khomaini; Bukhari Daud; Nira Erdiana (Universitas Syiah Kuala, 2019)
Speaking is one of language skills required to learn for all senior high school students. SMAN 4 Wira Bangsa Meulaboh is one of senior high schools whose students have a good speaking proficiency as they succeed in winning some competition held in West Aceh regency. This study aimed at finding out the techniques mostly used by English teachers to teach speaking at SMAN 4 Wira Bangsa Meulaboh. This study was a qualitative study. Total sampling technique was employed to select three English teachers at SMAN 4 Wira Bangsa Meulaboh. The instrument used to collect the data was interview. The result showed that there was no dominant technique used by English teachers at SMAN 4 Wira Bangsa. They used debate technique, role play and jigsaw. The teachers also said that they frequently change the techniques based topic of the subject. The interview results also indicated that all of the teachers tried to present authentic material to the speaking class. Based on the interview, it was also obtained that the common mistakes did by English teachers were overused of mother tongue and choosing technique without considering the students’ level. It is expected that the teachers do collaborative work in determining which technique work better to certain topic compared to other techniques.